A GIS-based methodology for identifying sustainability conflict areas in mine design – a case study from a surface coal mine in the USA. Issue 3 (3rd May 2016) - Craynon, John R.; Sarver, Emily A.; Ripepi, Nino S.; Karmis, Michael E.
Abstract : Through proper design, coal mining operations can contribute to the social, economic and environmental aspects of sustainable development. The regulatory and permitting programmes for coal mining in the United States, which often focus on several largely environmental parameters, are barriers to holistic consideration of these three sustainability pillars. Some changes in the current US regulatory framework may be necessary to allow for systematic consideration of economic, environmental and social factors in order to achieve more sustainable development of mineral and energy resources. In the quest towards more sustainable mining activities, it has been suggested that mine design may be optimised in the context of sustainability using a systems engineering approach that simultaneously considers economic, environmental and social factors. The use of geographic information system (GIS) tools may aid in this approach by allowing for spatial analyses of various resources (e.g. mineral values, water resources, community infrastructure) and identification of potential areas of conflict between these factors. By GIS analysis of the on-the-ground issues related to sustainability, the key parameters to be considered in decision-making were identified. This type of analysis is crucial not only for regulatory compliance, but also to ensure that the operation has obtained the 'social licence' to mine. To demonstrate this approach, a case study was conducted on a mountaintop coal mining operation in central Appalachia. High-conflict areas were found to be primarily concentrated near streams and residential developments through the use of GIS. The case study suggests that use of this approach could have allowed for better communications and planning. The controversies surrounding permitting at the site, including litigation, could have also been avoided. Adoption of such a process could assist in the transition to a new regulatory framework that promotes and is based on sustainable development principles.